The Anti-Inflammatory Effect of Alpha-1 Antitrypsin in Hepatocyte Transplantation. (July 2018) - Lee, Charlotte; Dhawan, Anil; Filippi, Celine; Mitry, Ragai R; Iansante, Valeria; Fernandez-Dacosta, Raquel; Lehec, Sharon; Chandrashekran, Anil; Strom, Terry; Koulmanda, Maria; Fitzpatrick, Emer
Abstract : Introduction: For patients with liver-based metabolic disorders, hepatocyte transplantation can be an effective bridge until a liver becomes available. However, long term function of transplanted hepatocytes has not been achieved. This is partly attributed to activation of the innate immune response that leads to rapid clearance of hepatocytes shortly after transplantation. Alpha-1 antitrypsin (AAT) is a natural immune modulator with anti-inflammatory and anti-apoptotic effects. Our aim was to determine if AAT could improve engraftment of transplanted hepatocytes and investigate the anti-inflammatory mechanisms involved. Methods: In Vitro : A tubing loop model was used to analyse activation of the immune response when human hepatocytes (HH) were in contact with ABO-matched blood and 4mg/ml AAT. Platelet and white cell counts, complement and cytokine expression were analysed. In vivo: Primary rat hepatocytes were isolated from 250g male Sprague Dawley rats. Female littermates underwent tail vein injection of AAT (120mg/kg) or saline (control) prior to the intrasplenic transplantation of 2x107 eGFP male hepatocytes. At 24h, 48h and 1wk, liver was collected for immunohistochemical analysis and DNA isolated for Y chromosome (SRY) gene expression. Hepatic mononuclear cells (HMNC's) were isolated and immune cell infiltration analysed using flow cytometry. Blood samples were used to analyse cytokine expression analysed using a Milliplex Map rat cytokine/bead panel. Results: I n Vitro: In the loop model, HH elicited a significant drop in platelet count with thrombus formation compared to blood only controls (51x109cell/L±15 vs 173x109cell/L±8, P<0.001. N=6). Loops containing AAT and HH showed no drop in platelet count with no thrombus formation (140x109cell/L±13, P>0.05. N=6). AAT decreased pro-inflammatory cytokines IL-1β(1.7vs3.9ng/ml), IL-6(0.4vs1.1ng/ml) and IFN-γ(0.4vs1.3ng/ml)(N=5, P<0.05) and had higher concentrations of anti-inflammatory IL-1RA compared to non-treated loops (913vs719ng/ml)(N=5, P<0.05). In vivo: There were significantly more eGFP hepatocytes in AAT treated livers compared to untreated at 24h and 48h (24hrs; 4.5±1.4% vs 1.0±0.2%, **P<0.01 and 48hrs 2.1±0.5 vs 1.0±0.3%, *P<0.05). Engraftment of male hepatocytes by analysis using SRY was 10-fold higher in the AAT treated group at 48h compared to control and 4-fold higher at 1wk (N=3). AAT decreased the percentage of CD86+ve activated macrophages compared to untreated controls at 48hrs (10% vs14.6%), 1-week (2.3% vs 6.9% and 1 month (2.1% vs 3.6%). AAT decreased concentrations of pro-inflammatory cytokines; IL-1β, IL-1, IL-6 and IL-2 compared to controls 1h post transplantation. Conclusions: AAT improves engraftment of transplanted hepatocytes by inhibition of inflammatory cytokines and immune cell infiltration. AAT may significantly prolong cell survival and function, improving the clinical outcomes of the technique for children with liver based metabolic disease.